Cluster Analysis in Women with Overactive Bladder Syndrome: Identification of Clinical Subgroups Based on Symptom Severity - Baran, Emine; Beksac, Mehmet Sinan; Ozgul, Nejat; Akbayrak, Turkan (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVE: The aim of this study was to classify women with overactive bladder (OAB) syndrome using cluster analysis based on symptom severity, quality of life related to urinary functions, and bladder diary data. STUDY DESIGN: This cross-sectional study included 62 women diagnosed with overactive bladder (OAB) syndrome and an Overactive Bladder Symptom Score (OABSS)≥10.5. Participants completed the OABSS, Incontinence Impact Questionnaire-7 (IIQ-7), Urogenital Distress Inventory-6 (UDI-6), and a three-day bladder diary. Cluster analysis was performed using the k-means algorithm based on symptom severity, quality of life, and bladder diary data. Differences between clusters were tested using the Kruskal-Wallis and Mann-Whitney U tests. RESULTS: The cluster analysis identified three distinct groups: the severe symptom cluster (n=17), the moderate symptom cluster (n=25), and the mild symptom cluster (n=20). The severe symptom cluster had the highest OABSS scores, the most frequent voiding episodes, and the lowest maximum voided volume (p<0.05). The mild symptom cluster exhibited the lowest OABSS scores, the best bladder function, and the highest IIQ-7 and UDI-6 scores (p<0.05). The moderate symptom cluster fell between the severe and mild clusters in terms of symptom severity. CONCLUSION: In this study, cluster analysis was used to classify OAB patients into subgroups based on symptom severity, quality of life-related to urinary function, and bladder function. As a result of the analysis, participants were categorized into three groups: severe - moderate - mild symptom clusters. It was determined that as symptom severity increased, bladder function deteriorated, and the impact on quality of life became more significant.